Efektifitas Konsumsi Jus Mentimun Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi - Dendy Kharisna; Wan Nisfha Dewi; Widia Lestari (Jurnal Ners Indonesia, 2012)
The aim of this research is to examine the effect of cucumber juice on blood pressure of hypertensive patients. The research usedquasy experimental design with non-equivalent control group design which devided into two groups, treatment group andcontrol group. The sampling technique explored purposive sampling with 30 hypertension patients which selected based oninclusion criteria. The sample devided into 15 people of treatment group and 15 people of control group. The patients oftreatment group were given a glass of cucumber juice everyday in a weeks. Where as control group, were not given. The equipmentwas used to measure blood pressure is sphygmomanometer. Data analysis applied were univariate and bivariate by usingdependent sample t test and independent sample t test to show the result. The result of this research showed that mean of meanartery pressure (MAP) of control group before drinking cucumber juice was 117,9 and mean of mean artery pressure (MAP)after drinking cucumber juice was 104,2 which means there was blood pressure difference arround 13,8 of this member with pvalue was 0,000 (less than 0,05). The conclusion is drinking cucumber juice could help patient with hypertension to reduce theirblood pressure.Key words : cucumber juice, blood pressure, hypertension